Analysis of Synergic Relationship in a Chilean Medium-Sized Port: An Approach from the Simulation of the Transformation Matrix of Eigenvalues - Duran-San Martin, C (Institute of Electrical and Electronics Engineers Inc., 2016)
Ports can be considered as a mixed network composed of different stakeholders such as private service provider companies, public organizations, professional and social associations. Each of them has its own aims and the port community exercises the role of coordinator, taking on responsibility for governance. In general, the interaction among the different actors generates strategic synergy, contributing to the achievement of greater efficiency in the port system. This study presents a method to identify the degree of synergy in a Chilean medium-sized port in the context of a micro and macro environment. Synergy involves political, economic, social, technological and environmental factors, including risk and organizational learning, which are evaluated as a multi-criteria system. A diagnostic research is done, including stakeholders and associated experts opinions, by applying a survey designed and based on an array of relationships among the actors. The results are processed to obtain the eigenvalues and eigenvectors of the matrix, which are interpreted as linear dependence/independence strategic relationships among the actors involved. To analyze the information obtained from the survey, a Correlation Matrix is created where we can identify synergy relationships. So, degrees of synergy between the Port Community and the other actors that integrate the Chilean medium-sized port system are explored. As a conclusion, a direct relationship exists between the degree of strategic synergy and the actors linkage to port operational activities. © 2016 IEEE.